Segmentation of passenger preferences for using digital technologies at airports in Norway - Halpern, Nigel; Mwesiumo, Deodat; Budd, Thomas; Suau-Sanchez, Pere; Bråthen, Svein (Elsevier, 2021)
Airports are increasingly focused on implementing digital technologies at key stages of the airport journey to enhance the passenger experience. However, passengers have different preferences. TwoStep Cluster Analysis is used to reveal the presence of distinct segments according to their preferences. The findings are based on a survey of 6082 passengers at airports in Norway. Three distinct segments are identified: those that prefer traditional manual processes, those that prefer automated technology-based processes, and those that prefer more personalised technology-based processes. Significant differences are revealed for each segment according to passenger and trip characteristics and opinions regarding how the use of digital technologies at airports impact on personal privacy and human dignity. The findings contribute to knowledge on passenger preferences at airports and can help to inform airport decision making
Keywords: Two Step cluster analysis; Airport experience; Digital technologies; Segmentation